Large-scale integration of photovoltaic power in a distribution grid using power curtailment and energy storage. (October 2017) - Luthander, Rasmus; Lingfors, David; Widén, Joakim
Highlights: Development of a method for managing large integration of PV in a distribution grid. Feed-in power limit for each PV system based on a voltage-power relationship. Power curtailment of PV systems and energy storage for overvoltage prevention. Validation with data from a distribution system with more than 5000 end-users. End-users affected by overvoltage reduced from 53% to 0% with 100% PV penetration. Abstract: Photovoltaic (PV) power generation is an important component for the future energy system. High penetration of PV power in a power distribution system might however lead to problems with overvoltage and overload. In this study, a method for PV power curtailment and placement of decentralized energy storage is developed to control voltage, feeder currents and distribution substation overloading. The method determines an individual feed-in power limit for each PV system owner based on a voltage-power relationship. Measured data from a 10 kV/400 V three-phase distribution grid in the Swedish municipality of Herrljunga with more than 5000 end-users and simulated PV electricity production data are used for a case study to verify the model. The method is evaluated for yearly PV electricity production of up to 100% of the yearly electricity consumption. The results show that the method is able to prevent overvoltage for all penetration levels in the studied distribution grid, reduce the number of feeders affected by overcurrent and lower the maximum load on the two substations.